Information disclosure in elections with sequential costly participation - Dmitriy Vorobyev (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2020)
Electoral legislation varies across countries and within countries over time, and across different types of elections in terms of how it allows publication of intermediate election results including turnout and candidates' vote shares during an election day. Using a pivotal costly voting model of elections in which voters have privately observed preferences between two candidates and act sequentially, I study how different rules for disclosing information about the actions of early voters affect the actions of later voters, and how they ultimately impact voter and candidate welfare. Comparing three rules observed in real life elections (no disclosure, turnout disclosure and vote count disclosure), I find that vote count disclosure dominates the other two rules in terms of voter welfare. I further show that each of the rules can provide a candidate with either the greatest or the least chance to win, depending on the candidate's ex-ante support.
urn:nbn:de:1-2020100511051221499142
Keywords: D71; D72; D83; 330; Voting; Participation; Information Disclosure